2021
DOI: 10.3390/ijms22115498
|View full text |Cite
|
Sign up to set email alerts
|

The Crossroads between Host Copper Metabolism and Influenza Infection

Abstract: Three main approaches are used to combat severe viral respiratory infections. The first is preemptive vaccination that blocks infection. Weakened or dead viral particles, as well as genetic constructs carrying viral proteins or information about them, are used as an antigen. However, the viral genome is very evolutionary labile and changes continuously. Second, chemical agents are used during infection and inhibit the function of a number of viral proteins. However, these drugs lose their effectiveness because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 173 publications
(193 reference statements)
0
8
0
Order By: Relevance
“…However, Cu has likewise been postulated to inactivate and degrade viral particles primarily through the generation of ROS, leading to the degradation of the viral genome and its proteins ( 37 ). An inactivation assay for H1N1 influenza virus (subtype of IAV) revealed that nucleoprotein (protein visualized through western blot) and HA (RNA quantified via reverse transcription-PCR) are imperceptible after 30 min of treatment with CuNPs ( 38 , 39 ). Furthermore, hybrid silver (Ag)-Cu NPs are capable of binding to glycoprotein gp120 at the HIV cell envelope and inhibiting infection in T cells in vitro ( 40 ).…”
Section: Copper Nanoparticles(cunps)mentioning
confidence: 99%
“…However, Cu has likewise been postulated to inactivate and degrade viral particles primarily through the generation of ROS, leading to the degradation of the viral genome and its proteins ( 37 ). An inactivation assay for H1N1 influenza virus (subtype of IAV) revealed that nucleoprotein (protein visualized through western blot) and HA (RNA quantified via reverse transcription-PCR) are imperceptible after 30 min of treatment with CuNPs ( 38 , 39 ). Furthermore, hybrid silver (Ag)-Cu NPs are capable of binding to glycoprotein gp120 at the HIV cell envelope and inhibiting infection in T cells in vitro ( 40 ).…”
Section: Copper Nanoparticles(cunps)mentioning
confidence: 99%
“…Apart from vaccines and drugs, the host metabolism has been targeted by some research into how to suppress the replication of influenza virus [ 69 ]. A variety of studies have indicated that copper-involved pathways in the host were effected after influenza virus infection [ 69 , 70 ].…”
Section: Copper Inactivate Influenza Virus By Targeting Key Viral Pro...mentioning
confidence: 99%
“…Apart from vaccines and drugs, the host metabolism has been targeted by some research into how to suppress the replication of influenza virus [ 69 ]. A variety of studies have indicated that copper-involved pathways in the host were effected after influenza virus infection [ 69 , 70 ]. Moreover, host cell copper transporters CTR1 and ATP7A have been demonstrated to be important for influenza virus replication, suggesting the role of copper in the influenza virus life cycle [ 71 ].…”
Section: Copper Inactivate Influenza Virus By Targeting Key Viral Pro...mentioning
confidence: 99%
“…Copper (Cu) is an essential micronutrient with two main biological functions, the first as a structural/catalytic cofactor of enzymes, and the second as a coactivator of key transcription factors [ 90 ]. Cu serves as a cofactor when present as an ion and is used in redox enzymatic reactions [ 91 ] or carrying out other functions such as the metabolism of biological amines, activation of neuropeptides, or cell respiration (cytochrome-c oxidase).…”
Section: Role Of Micronutrients During the Viral Infection Of Sars-cov-2mentioning
confidence: 99%
“…During the first stage of H5N1 influenza virus replication, virus-induced disruption of cytosolic Cu/Zn-SOD formation [ 95 ] unbalances the oxidative process and ATP7A, a protein that imports [Cu1 +] into trans-Golgi–derived compartments, is required for the synthesis of influenza viral RNA and proteins [ 96 ]. In vitro studies show a link between host proteins that transport Cu into the cell (CTR1) and the secretory pathway (ATP7A), with their role in influenza A (H1N1) virus protein and RNA synthesis [ 90 ].…”
Section: Role Of Micronutrients During the Viral Infection Of Sars-cov-2mentioning
confidence: 99%